2015
DOI: 10.1111/pace.12678
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Epicardial and Endocardial Cardiac Resynchronization Therapy on Transmural Dispersion of Repolarization

Abstract: ms, P = 0.89) in both groups. Compared to transseptal endocardial CRT, epicardial CRT was associated with a significant increase in ± 18.9 ms, P = 0.01) and P = 0.04).Conclusion: Transseptal LV endocardial pacing is associated with significant reduction in TDR characteristics compared to epicardial pacing in CRT. Further studies are warranted to determine whether these effects may contribute to reduction of arrhythmias in patients with CRT. (PACE 2015; 0:1-7) cardiac resynchronization therapy, transmural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
4
1
1
Order By: Relevance
“…Under physiological condition, hearts depolarize from endocardium to epicardium, and repolarize in an opposite direction35. However, CRT totally changes left ventriclular direction of depolarization and repolarization since its epicardial pacing, leading to TDR increasing36. It was reported that occurrence of tachycardia was higher in early stage of CRT implantation37.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological condition, hearts depolarize from endocardium to epicardium, and repolarize in an opposite direction35. However, CRT totally changes left ventriclular direction of depolarization and repolarization since its epicardial pacing, leading to TDR increasing36. It was reported that occurrence of tachycardia was higher in early stage of CRT implantation37.…”
Section: Discussionmentioning
confidence: 99%
“…Lead V5 or lead II (if lead V5 was unsuitable) was used for analysis. The QT interval was defined as the time from the beginning of the QRS complex to the end of the T wave ( 19 ). The QT interval was corrected and measured according to the Bazett’s formula ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Increased TDR measured by the T peak -T end (Tp-Te) and Tp-Te/QT ratio has been associated with a higher incidence of ventricular arrhythmias in patients who have received a CRT-D ( 18 ). CRT with trans-septal LV endocardial CRT increases the physiological activation and is associated with a significant reduction in the TDR characteristics compared with those in conventional epicardial pacing in CRT ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kleinere Studien haben einen Vorteil für die endokardiale linksventrikuläre Stimulation gezeigt [32][33][34]. So zeigt die endokardiale linksventrikuläre Stimulation signifikant geringere Erregungsdispersionen in Form schmalerer QRS-Breiten im Vergleich zu epikardialer linksventrikulärer Stimulation [35,36].…”
Section: Epikardiale Vs Endokardiale Linksventrikuläre Stimulationunclassified